Silicon satellite spectra from laser imploded microballoons - LUNNEY, JAMES GERARD (American Physical Society, 1981)
The dielectronic satellite spectral lines, on the long-wavelength side of the hydrogenic Si XIV Lyman-? line, have been observed in the space-resolved spectra from laser-imploded glass microballoons. In the electron density range 1?1022 to 2?1023 cm-3, the intensities of the Si XIII 2s 2p P3-1s 2s S3 and 2p2 P3-1s2p P3 satellite lines increase with density in agreement with numerical modeling. These satellite lines are a promising density diagnostic for the imploded glass plasma.
PUBLISHED
Keywords: Physics